Penggunaan Media Pembelajaran dalam Meningkatkan Motivasi Belajar Siswa Bidang Studi IPS - Nurrahmah, Nurrahmah; Turmuzi, Ahmad; Deni, Sutra; Yakin, Nurul; Anam, M Chairul (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2024)
This study aims to examine the use of learning media in enhancing student motivation in the subject of Social Studies Geography at MA Darul Ijtimak Lombok Tengah for the academic year 2020/2021. The data collection methods used were observation, interviews, and documentation. The data analysis technique employed was qualitative analysis. The findings indicate that the use of learning media, especially maps, can enhance student motivation. The application of map media in Social Studies Geography lessons makes students more enthusiastic and prevents them from becoming bored or uninterested, thus making the teaching and learning process more engaging and effective.